Characterization of Activated Carbon from Coffee Husk Using Potassium Hydroxide (KOH) as an Activator - Putra , Tamam Athallah Rhely; Yunira, Eka Nur'azmi; Pratama, Borneo Satria; Witoyo, Jatmiko Eko; Pangestuti , Martasari Beti; Putra, Endo Pebri Dani; Nugraha, Aditya Wahyu; Devita, Wilda Harlia (Universitas Brawijaya, 2025)
Coffee husk is an agricultural by-product of coffee production, and its utilization is still limited. So, the study focuses on the potential of coffee husk to be turned into activated carbon. An essential step in producing activated carbon is activation, primarily performed using chemical solvents, such as potassium hydroxide (KOH). However, there are still limited studies on the effect of KOH concentration on the activation of charcoal from coffee husk. Therefore, the study aims to determine the impact of potassium hydroxide (KOH) concentrations on the characteristics of activated carbon derived from coffee husk. The KOH concentration ranges used to activate charcoal were 0 M (as control), 1 M, and 2 M, and were conducted using the completely randomized design (CRD) approach. The characteristics of the activated carbon were analyzed according to the SNI 06-3730-1995 standard, including moisture content, ash content, volatile matter content, and bonded carbon content. The results indicated that KOH concentration significantly impacted the characteristics of activated carbon derived from coffee husk.